Desire as a theory for migration studies: temporality, assemblage and becoming in the narratives of migrants - Collins, Francis L. (Journal of ethnic and migration studies, 2018)
This article explores the potential of desire as a conceptual vocabulary to enliven scholarly understandings of migrant mobilities. Desire and questions of human aspiration draw our attention to the generative potential of migration, not only the myriad forces that make migration possible but also the transformative possibilities for the subjects and spaces involved. By focusing on desire, then, it becomes possible to reconceptualise migration as an ongoing process of spatio-temporal differentiation rather than as a univalent and knowable phenomenon. The process of migration is in this respect also tied up with a concomitant process of becoming for migrants themselves, a transformation in subjectivity that also involves transformations for the places they move through and the people they move with. This article unpacks these conceptualisations of migration through three individual narratives of migration from Southeast Asia to South Korea. Through these narratives the article highlights three dimensions of migration that can be re-examined through the analytical emphasis on desire: the multiple temporalities of migrant lives and future potential; the assemblage of spatialities and relations articulated in migration; and the politics of migration that is generated through the enlisting of migrants by states and migrants' own desire for becoming through migration.